Obtención y caracterización de carbón activado a partir de la vaina de Delonix regia (ponciana) mediante activación química ácida y básica - Carranza Calderón, Miguel Alejandro (2019)
In the present investigation, the obtaining and characterization of activated carbon from the Delonix regia pod will be carried out, through the activation with phosphoric acid, potassium hydroxide and sodium hydroxide with impregnation ratios of raw material / activating agent by weight of 1 / 1, 1/2, 2/1, 1/5 and 5/1, for 2 hours and 600 ° C, in order to determine the yield and adsorption capacity of activated carbon; obtaining the highest yield value of 22.93% and iodine number of 776 mL iodine solution adsorbed / g activated carbon for activated carbon with phosphoric acid with an impregnation ratio by weight raw material phosphoric acid 1/5. Similarly, the highest index of methylene blue corresponds to activated carbon with potassium hydroxide with 17.75 mL methylene blue solution / 0.1 g of activated carbon at the impregnation ratio by weight 1/5 raw material / potassium hydroxide. It is concluded that the activated carbon obtained with phosphoric acid has the best adsorption capacity and best yield